Аналіз забезпечення захисту інформації в життєвому циклі розробки програмних Web продуктів - Качан, В. Є.; Марчук, А. В. (ХНУРЕ, 2023)
In the modern world, web products have taken an important place in people's lives. Thousands of online websites and applications serve customers around the world, raising questions about the security of these products. A necessary aspect of its provision is the use of appropriate solutions in the development and implementation process. This work identifies the need to use a safe development life cycle and the corresponding risks of its absence. A laboratory setup was developed that allows automating most stages of SSDLC and simulates the processes of source code version control, quality control, application assembly and deployment, launch of vulnerability scanners, etc.
Keywords: розробка програмних Web продуктів; забезпечення захисту інформації